The role of the globalisation process on mitigation of carbon dioxide emissions of Latin American & Caribbean countries - Koengkan, Matheus; Fuinhas, José Alberto (Cadernos UniFOA, 2021)
The impact of globalisation on carbon dioxide emissions was analysed in a panel data of thirteen LAC countries for the period from 1991 to 2012. A panel autoregressive distributed lag methodology was used to decompose the total effects of globalisation on carbon dioxide emissions both in short- and long-run components. There is evidence that globalisation contributes to reducing carbon dioxide emissions in the long-run. A possible explanation of this result is that the process of globalisation causes technological enhancement in LAC countries, which contributes to a decrease in environmental degradation. Globalisation has other implications, such as the transfer of responsibility from the state to the private sector, where this transfer corresponds to the shifting of regulatory attributes to independent governmental regulatory authorities, in other words, “regulation for competition”.